2003
DOI: 10.1029/2002gl016717
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton bloom in the Bay of Bengal during the northeast monsoon and its intensification by cyclones

Abstract: Satellite derived chlorophyll a imageries are used to present a phytoplankton bloom in the Bay of Bengal during the northeast monsoon (November–February) and the mechanisms that can upwell nutrients to sustain the bloom are investigated using sea level anomalies and winds. OCTS and SeaWiFS chlorophyll a images show that there is a phytoplankton bloom in the southwestern part of the bay during November–January. The chlorophyll a concentration of the bloom can be as high as 2 mg m−3 compared to near zero value b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
141
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(149 citation statements)
references
References 19 publications
8
141
0
Order By: Relevance
“…However, the winds, though strong in the northern Bay of Bengal, were unable to break the stratification and initiate deep wind mixing as inferred from the static stability parameter. A similar result was arrived at by Shenoi et al (2002) based on kinetic energy and by Vinayachandran et al (2002) in the context of barrier layer formation (see also Thadathil et al, 2007). Using modelling, Han et al (2001) also obtained a thin mixed layer in the region where precipitation exceeded evaporation.…”
Section: Summary and Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…However, the winds, though strong in the northern Bay of Bengal, were unable to break the stratification and initiate deep wind mixing as inferred from the static stability parameter. A similar result was arrived at by Shenoi et al (2002) based on kinetic energy and by Vinayachandran et al (2002) in the context of barrier layer formation (see also Thadathil et al, 2007). Using modelling, Han et al (2001) also obtained a thin mixed layer in the region where precipitation exceeded evaporation.…”
Section: Summary and Discussionsupporting
confidence: 50%
“…While comparing the total kinetic energy available for mixing in the Arabian Sea and the Bay of Bengal, Shenoi et al (2002) stated that the shallow mixed layer depth in the Bay of Bengal during the summer monsoon is primarily driven by a combination of weaker winds and strong near-surface stratification. Subsequently, Vinayachandran et al (2002) argued that strong stratification associated with the barrier layer curtails the vertical mixing leading to the formation of a shallow mixed layer. In contrast, with help of a one-dimensional turbulent closure model Prasad (2004) studied the physical mechanism governing the seasonal evolution of mixed layer depth along two transects along the central Arabian Sea and Bay of Bengal and concluded that the surface forcing controls mixed layer depth in the Bay of Bengal rather than the vertical salinity stratification.…”
Section: Introductionmentioning
confidence: 99%
“…The fresh water inputs result in the stratification of the upper 50 m of the water column (Kumar et al 2002). Moreover, the frequently occurring cyclones are additional sources of phosphate and nitrates in the surface waters of the Bay (Vinayachandran and Mathew 2003). This nutrient supply results in the formation of intense localized blooms.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…Strong winds and torrential rain are typical components of typhoons that disrupt the natural environment. Strong wind-induced vertical mixing and upwelling pump nutrients (carbon, nitrogen, phosphorus and silicon) from deep water, and enhance chlorophyll a concentration (Vinayachandran and Mathew, 2003;Walker et al, 2005;Byju and Kumar, 2011;Hung and Gong, 2011). Abrupt torrential rain contributes to the concentrated influx of organic carbon and nutrients to the ocean (West et al, 2011), which is considered as the main cause of the post-storm increase in phytoplankton growth and primary production in coastal and estuary ecosystems (Chang et al, 1996;Shiah et al, 2000;Paerl et al, 2006).…”
Section: Introductionmentioning
confidence: 99%